EPOS AND HISTORIES (on the example of national versions of the epic "Edige") - Allambergenov, K. (SCIENCE and SOCIETY, 2023)
This report provides a comparative typological analysis of the idea of national independence, which is reflected in the national versions of the Edige epic.